Susceptibility of Vero cell line to vaccine strains of the measles virus - Takata, Célia Sayoko; Kubrusly, Flávia Saldanha; Miyaki, Cosue; Mendes, Inácio França; Rizzo, Edda de (Revista de Saúde Pública, 1994)
Vero cells used by distinct measles vaccine control laboratories had their susceptibility to Moraten, Schwarz and Biken CAM-70 vaccine strains assayed. Of a total of 72 lots of measles vaccine whose potency was titrated by microtechnique in two Vero cell samples (Vero IB and Vero INCQS), 25 had been produced with Moraten strain, 24 with Schwarz and 23 with Biken CAM-70. The statistical analysis of the results demonstrated that both Vero cells assayed presented comparable susceptibility to Moraten and Biken CAM-70 strains. As to the Schwarz strain, Vero IB cells were more susceptible than the other cell sample tested, thus confirming the existence of different sensitivities of Vero cells to some measles vaccine strains, or even to viruses derived from the same strain but with different passage histories. An altered cell susceptibility to virus replication may significantly alter the results in potency testing. Such alteration may be caused not only by the adoption of distinct protocols for the maintenance of cell cultures by different control laboratories but also by the methodology followed in the vaccine titration. In order to minimize the differences existing among the results obtained in the potency testing, it is suggested that all control laboratories should use the same protocols for cell culture maintenance as well as for vaccine potency testing.